Análisis de potencialidad turística y su impacto en el desarrollo local en el cantón Marcabeli provincia de El Oro. - Valarezo Granda, Paolo Alfredo (Machala : Universidad Técnica de Machala, 2024)
This degree work called "Analysis of Tourism Potential and its Impact in the Marcabelí Canton of the Province of El Oro" explores the tourism potential of Marcabelí, a canton located in the province of El Oro, Ecuador. The study highlights the importance of tourism as a key economic and social activity for the sustainable development of local communities, in this case, Marcabelí, which has a variety of natural and cultural resources that can be used for tourism purposes. The research uses a mixed methodology, combining quantitative and qualitative techniques to evaluate the tourism potential of the canton. The techniques applied include direct observation, interviews and surveys of the local community, and documentary analysis based on information provided by the Ministry of Tourism of Ecuador. An inventory and ranking of the natural and cultural resources of Marcabelí was carried out, and the community's orientation towards tourism development was identified through interviews. The characteristics of the canton such as strengths, opportunities, weaknesses and threats were also analyzed. The inventory of tourist resources allowed the attractions of Marcabelí to be categorized into different hierarchies, identifying those of greatest relevance and potential to be exploited for tourism. Through a SWOT analysis (Strengths, Weaknesses, Opportunities and Threats), both internal and external factors that can influence the tourism development of the canton were considered. The analysis revealed that Marcabelí has ​​a combination of natural and cultural attractions such as: La chorrera El Rocío, the Puyango River, the Mother Church and its traditions that, if properly managed, can turn the canton into a quality tourist destination. Marcabelí presents a rich diversity of landscapes, biodiversity, favorable climate and attractive geography, all elements that make it an ideal place for ecotourism and cultural tourism. Furthermore, local culture, including traditions, gastronomy and festivities, adds significant value to cultural tourism in the region. Agrotourism also emerges as an important opportunity, given that the region has significant agricultural activity such as livestock farming. This type of tourism would not only allow visitors to participate in agricultural activities, but would also promote a greater appreciation for rural traditions and contribute to diversifying the local economy through certified tourist communities. Although Marcabelí has ​​high tourism potential, it also faces challenges that must be addressed to ensure sustainable development. Among these challenges are the need to improve tourism infrastructure, increase accessibility and strengthen local capacities through training and education programs. Additionally, it is crucial to develop effective marketing and promotional campaigns that highlight Marcabelí's unique characteristics and its commitment to sustainability. The study concludes that, through proper planning and collaboration between the government and the community, Marcabelí can develop quality tourism products that attract a significant number of visitors. This would not only benefit the region economically, but would also contribute to the preservation of its natural and cultural resources, ensuring sustainable and equitable tourism development.
Este trabajo de titulación denominado "Análisis de Potencialidad Turística y su Impacto en el Cantón Marcabelí de la Provincia de El Oro" explora el potencial turístico de Marcabelí, un cantón ubicado en la provincia de El Oro, Ecuador. El estudio subraya la importancia del turismo como una actividad económica y social clave para el desarrollo sostenible de las comunidades locales, en este caso, Marcabelí, que cuenta con una variedad de recursos naturales y culturales que pueden ser aprovechados para fines turísticos. La investigación utiliza una metodología mixta, combinando técnicas cuantitativas y cualitativas para evaluar las potencialidades turísticas del cantón. Entre las técnicas aplicadas se incluyen la observación directa, entrevistas y encuestas a la comunidad local y análisis documental basado en información proporcionada por el Ministerio de Turismo de Ecuador. Se realizó un inventario y jerarquización de los recursos naturales y culturales de Marcabelí, y se identificó la orientación de la comunidad hacia el desarrollo turístico mediante entrevistas, también se analizaron las características del cantón como fortalezas, oportunidades, debilidades y amenazas. El inventario de recursos turísticos permitió categorizar los atractivos de Marcabelí en diferentes jerarquías, identificando aquellos de mayor relevancia y potencial para ser explotados turísticamente. A través de un análisis FODA (Fortalezas, Oportunidades, Debilidades y Amenazas), se consideraron tanto los factores internos como externos que pueden influir en el desarrollo turístico del cantón. El análisis reveló que Marcabelí posee una combinación de atractivos naturales y culturales como: La chorrera El Rocío, el Río Puyango, la Iglesia Matriz y sus tradiciones que, si se gestionan adecuadamente, pueden convertir al cantón en un destino turístico de calidad. Marcabelí presenta una rica diversidad de paisajes, biodiversidad, clima favorable y una geografía atractiva, todos elementos que lo convierten en un lugar ideal para el ecoturismo y el turismo cultural. Además, la cultura local, que incluye tradiciones, gastronomía y festividades, añade un valor significativo al turismo cultural en la región. El agroturismo también emerge como una oportunidad importante, dado que la región cuenta con una actividad agrícola significativa como la ganadería. Este tipo de turismo no solo permitiría a los visitantes participar en actividades agrícolas, sino que también promovería un mayor aprecio por las tradiciones rurales y contribuiría a diversificar la economía local a través de comunidades turísticas certfiicadas. Aunque Marcabelí tiene un alto potencial turístico, también enfrenta desafíos que deben ser abordados para garantizar un desarrollo sostenible. Entre estos desafíos se encuentran la necesidad de mejorar la infraestructura turística, aumentar la accesibilidad y fortalecer las capacidades locales a través de programas de capacitación y educación. Además, es crucial desarrollar campañas de promoción y marketing efectivas que resalten las características únicas de Marcabelí y su compromiso con la sostenibilidad. El estudio concluye que, mediante una planificación adecuada y la colaboración entre el gobierno y la comunidad, Marcabelí puede desarrollar productos turísticos de calidad que atraigan a un número significativo de visitantes. Esto no solo beneficiaría económicamente a la región, sino que también contribuiría a la preservación de sus recursos naturales y culturales, asegurando un desarrollo turístico sostenible y equitativo.
Keywords: RECURSOS NATURALES; RECURSOS CULTURALES; TURISMO; PLANIFICACION DEL TURISMO